2022
DOI: 10.34172/ddj.2022.07
|View full text |Cite
|
Sign up to set email alerts
|

Review of Alloy Containing Bismuth Oxide Nanoparticles on X-Ray Absorption in Radiology Shields

Abstract: Background: Managing potential risks that can threaten the health of medical staff including risks associated with treatment tools and equipment has always played an important role in the healthcare systems. This study aimed to investigate the documentation on the effect of nanoparticle shields on the absorption of hazardous radiation in radiology, and specifically alloy containing bismuth oxide )Bi2O3) nanoparticles. Materials and Methods: Several databases including ScienceDirect, Web of Science, Scopus, Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Bismuth-213, with a half-life of 45.6 min, is a clinically used α-emitter in radioimmunotherapy. Clinical trials of 213 Bi-lintuzumab have shown that its administration against relapsed and refractory (R/R) acute myeloid leukemia (AML) was safe for healthy cells and led to remissions without significant extramedullary toxic effects [100][101][102]. 213 Bi-lintuzumab has shown quick targeting of disease locations.…”
Section: Bismuthmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth-213, with a half-life of 45.6 min, is a clinically used α-emitter in radioimmunotherapy. Clinical trials of 213 Bi-lintuzumab have shown that its administration against relapsed and refractory (R/R) acute myeloid leukemia (AML) was safe for healthy cells and led to remissions without significant extramedullary toxic effects [100][101][102]. 213 Bi-lintuzumab has shown quick targeting of disease locations.…”
Section: Bismuthmentioning
confidence: 99%
“…213 Bi-lintuzumab has shown quick targeting of disease locations. Bi 2 O 3 is lightweight and effective in protecting against ionizing radiations such as γ-rays, making it a promising agent for medical imaging and radiation therapy [102].…”
Section: Seleniummentioning
confidence: 99%